2009
DOI: 10.2353/ajpath.2009.090016
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HO-1 Protects against TNF-α-Mediated Airway Inflammation by Down-Regulation of TNFR1-Dependent Oxidative Stress

Abstract: Oxidative stresses are believed to play an important role in the induction of both cell adhesion molecules and pro-inflammatory cytokines, a key event in a variety of inflammatory processes. The enzyme heme oxygenase-1 (HO-1) functions as an antioxidant and serves to protect against tissue injury. In this study, we report that HO-1 was induced in cultured human tracheal smooth muscle cells after either treatment with a potent inducer of HO-1 activity, cobalt protoporphyrin IX, or infection with a recombinant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
151
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 32 publications
(52 reference statements)
5
151
1
Order By: Relevance
“…The regulation of HO-1 is biphasic and as a response to oxidative stress, HO-1 is upregulated within 6 h (Risom et al 2003;Sunil et al 2013). At later time points (including in the lung), HO-1 is involved in suppressing inflammation and initiating wound healing (Lee et al 2009;Ryter et al 2006), which may be the reason for a comparable upregulation in the groups of allergic mice.…”
Section: Effects Of Ozone and Ozone-limonene Reaction Products On Senmentioning
confidence: 95%
“…The regulation of HO-1 is biphasic and as a response to oxidative stress, HO-1 is upregulated within 6 h (Risom et al 2003;Sunil et al 2013). At later time points (including in the lung), HO-1 is involved in suppressing inflammation and initiating wound healing (Lee et al 2009;Ryter et al 2006), which may be the reason for a comparable upregulation in the groups of allergic mice.…”
Section: Effects Of Ozone and Ozone-limonene Reaction Products On Senmentioning
confidence: 95%
“…Increased HO-1 activity is found protective against inflammation, excessive cell proliferation and interstitial fibrosis [29] . Previous study suggested HO-1 could protect against airway inflammation by down-regulating tumor necrosis factor receptor (TNFR)1 dependent oxidative stress [30] . In asthma particularly, it was considered that the increase of HO-1 expression and activity were protective [31] .…”
Section: Discussionmentioning
confidence: 99%
“…c-Src has been shown to regulate ICAM-1 expression in various cell types (9,16). In addition, LPS can mediate c-Src activation and then cause the inflammatory responses (7,10).…”
mentioning
confidence: 99%
“…Raised levels of adhesion molecules might contribute to the recruitment of PMNs to the regions of inflammatory tissue. These adhesion molecules are classified into two major families: the Ig superfamily [e.g., ICAM-1 and VCAM-1] and the selectins (e.g., P-selectin and E-selectin) (9). ICAM-1 is an inducible cell surface glycoprotein on several cell types, which mediates the tight adhesiveness of PMNs and thus facilitates PMN migration across the vascular endothelium barrier and then interacts with lung epithelium (8).…”
mentioning
confidence: 99%